Safety and efficacy of recanalization therapy in pediatric stroke: A systematic review and meta-analysis. (November 2018) - Pacheco, Juliana T.; Siepmann, Timo; Barlinn, Jessica; Winzer, Simon; Penzlin, Ana Isabel; Puetz, Volker; von der Hagen, Maja; Barlinn, Kristian
Abstract: Background and purpose: Safety and efficacy of intravenous (IV) thrombolysis and endovascular therapy in children with acute ischemic stroke (AIS) are unknown to date. We aimed to review and synthesize currently available evidence on these acute recanalization therapies in pediatric stroke patients. Methods: We performed a systematic review and meta-analysis of all available data on safety and efficacy of acute treatment including thrombolysis and endovascular therapy in pediatric AIS patients aged <18 years. We searched the electronic databases Medline and Cochrane Library for eligible studies published from the earliest date available until August 31, 2016. Safety outcomes included intracerebral hemorrhage (ICH) post-treatment and in-hospital mortality. Efficacy outcomes included functional outcome 3–6 months after index stroke. Results: We identified 222 records, of which 3 studies with a total of 16, 987 pediatric stroke patients met our eligibility criteria of whom 181 received IV thrombolysis. No data exists from randomized trials and no data is available on endovascular thrombectomy. Risk of any ICH was increased in children receiving thrombolysis (risk ratio = 3.48, 95%CI: 1.66–7.29; p = 0.001) compared with controls, with no evidence of heterogeneity ( I 2  = 0%). None of the included studies reported complete data on symptomatic ICH. In-hospital mortality was similar between pediatric stroke patients treated with thrombolysis and controls (risk ratio = 1.44, 95%CI: 0.39–5.40; p = 0.586), with evidence of heterogeneity ( I 2  = 62%). Efficacy of revascularization therapies could not be analyzed due to lack of outcome data. Conclusions: Our analyses demonstrate a substantial lack of data on efficacy and safety of acute recanalization therapies in children with AIS. PROSPERO Registration Information: URL:http://www.crd.york.ac.uk/PROSPERO . Unique identifier: CRD42016047140. Highlights: Substantial lack of evidence for recanalization therapies in children with acute ischemic stroke. No adequate data on occurrence of symptomatic intracerebral hemorrhage following recanalization therapy. Non-uniformity in post-stroke assessment of functional recovery complicates any attempt to synthesize data on efficacy.